Changes in Physiological and Pathological Behaviours Produced by Deep Microelectrode Implantation Surgery in Rats: A Temporal Analysis - Gustavo A. Chiprés-Tinajero; Miguel A. Núñez-Ochoa; Laura Medina-Ceja (Behavioural Neurology)
Physiological behaviours such as the sleep-wake cycle and exploratory behaviours are important parameters in intact and sham-operated animals and are usually thought to be unaffected by experimental protocols in which neurosurgery is performed. However, there is insufficient evidence in the literature on the behavioural and cognitive effects observed after deep microelectrode implantation surgery in animal models of neurological diseases. Similarly, in studies that utilize animal models of neurological diseases, the impact of surgery on the pathological phenomena being studied is often minimized. Based on these considerations, we performed a temporal analysis of the effects of deep microelectrode implantation surgery in the hippocampus of rats on quiet wakefulness, sleep, and exploratory activity and the pathological behaviours such as convulsive seizures according to the Racine scale. Male Wistar rats (210-300 g) were used and grouped in sham and epileptic animals. Single doses of pilocarpine hydrochloride (2.4 mg/2 μl; i.c.v.) were administered to the animals to generate spontaneous and recurrent seizures. Deep microelectrode implantation surgeries in both groups and analysis of Fast ripples were performed. Physiological and pathological behaviours were recorded through direct video monitoring of animals (24/7). Our principal findings showed that in epileptic animals, one of the main behaviours affected by surgery is sleep; as a consequence of this behavioural change, a decrease in exploratory activity was also found as well as the mean time spent daily in seizures of scale 4 and the number of seizure events of scales 4 and 5 was increased after surgery. No significant correlations between the occurrence of FR and seizure events of scale 4 (rho 0.63, p value 0.25) or 5 (rho -0.7, p value 0.18) were observed. In conclusion, microelectrode implantation surgeries modified some physiological and pathological behaviours; therefore, it is important to consider this fact when it is working with animal models.